(untitled) (Research, Society and Development, 2022)
Objective: to investigate studies found in the scientific/academic environment that relate self-efficacy or self-concept with young soccer athletes. Method: The scope review was carried out using the methodology developed by the Joanna Briggs Institute (JBI) and includes studies on research platforms. Studies published in English, Spanish, Portuguese were considered, using a 10-year date limit on surveys, gray literature, theses and dissertations. The search strategy followed the natural process of document tracking, with the search carried out in the following databases: CAPES, BVS, SportDiscus, Eric, Pepsic and PsychINFO journals. The descriptors “self-efficacy”, “self-concept”, “soccer”, “young athletes” and “collective sports” were used. Result: Eleven articles were selected, these being of interest in the relationship of self-efficacy with young soccer athletes or those related to another sport. Conclusion: In these articles, we find a series of studies that have different methodologies to explore these questions. It is interesting to note that the studies involve several elements that are part of the sporting context, such as: family and coaches, key players for the athlete’s sporting success. The works do not have a single form of investigation, which shows how this topic can be subjected to various forms of analysis and researched in different ways. After the selection and analysis process, no studies were found that relate self-concept to young soccer athletes.